2022
DOI: 10.1111/dom.14767
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes subgroups and response to glucose‐lowering therapy: Results from the EDICT and Qatar studies

Abstract: Aim To examine the efficacy of glucose‐lowering medications in subgroups of patients with type 2 diabetes mellitus (T2DM). Research design and methods Cluster analysis was performed in participants in the Efficacy and Durability of Initial Combination Therapy for Type 2 Diabetes (EDICT) study and the Qatar study using age, body mass index (BMI), glycated haemoglobin (HbA1c), and homeostatic model assessment of insulin resistance (HOMA‐IR) and beta‐cell function (HOMA‐β). Participants also underwent an oral glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…This is confirmed by the many metabolites discussed above that are related to insulin resistance. Results from Qatari patients with severe insulin resistance showed that these patients did not respond adequately to insulin sensitizers such as metformin [ 75 ]. This may explain the low efficacy of metformin in the case of severe insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…This is confirmed by the many metabolites discussed above that are related to insulin resistance. Results from Qatari patients with severe insulin resistance showed that these patients did not respond adequately to insulin sensitizers such as metformin [ 75 ]. This may explain the low efficacy of metformin in the case of severe insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…4,10 FCP has been shown to be an equivalent cluster variable to originally used HOMA2 parameters for the assignation of participants into the four T2D subphenotypes. 6,9 All clinical outcomes (HbA1c, FPG, glycaemic outcome achievement, insulin dose, hypoglycaemia, body weight) were assessed at baseline and over the 26-week study period following the introduction of either IGlar-300 or IGlar-100, administered once-daily before bedtime, and titrated once-weekly to achieve a target FPG of <5.6 mmol/L (<100 mg/dl). Hypoglycaemia was determined according to the international consensus on definition as agreed by ADA/ EASD 12 using a confirmed plasma glucose (PG) value of ≤3.9 mmol/L (level 1) and <3.0 mmol/L (level 2) (≤70 or <54 mg/dl).…”
Section: Methodsmentioning
confidence: 99%
“…Variables that included age at onset of known diabetes, HbA1c, body mass index (BMI) and fasting C‐peptide (FCP) at baseline were scaled and centred for each participant and then assigned to one of the four T2D subphenotypes to which they were most similar, as estimated by the smallest Euclidean distance to subphenotype centroids derived from ANDIS coordinates 4,10 . FCP has been shown to be an equivalent cluster variable to originally used HOMA2 parameters for the assignation of participants into the four T2D subphenotypes 6,9 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations